The efficacy of immunonutrition in improving tolerance to chemoradiotherapy in patients with head and neck cancer, receiving nutritional counseling: study protocol of a randomized, open-label, parallel group, bicentric pilot study. (September 2021) - Caccialanza, Riccardo; Cereda, Emanuele; Klersy, Catherine; Nardi, Mariateresa; Masi, Sara; Crotti, Silvia; Cappello, Silvia; Caissutti, Valentina; Brovia, Carlotta; Lobascio, Federica; Formisano, Elena; Colombo, Sara; et al.
Background: Nutritional support, including nutritional counseling and oral nutritional supplements (ONSs), has been recommended at the earliest opportunity in head and neck (H&N) cancer patients. The limited available evidence on the efficacy of immunonutrition during chemoradiotherapy (CT-RT) in H&N cancer patients is positive with regard to some secondary endpoints, but is still scanty, particularly with regard to toxicity and treatment tolerance. We hypothesize that early systematic provision of ONSs with a high-protein–high-calorie mixture containing immunonutrients (Impact) compared to standard high-calorie–high-protein nutritional blends, in addition to nutritional counseling, may be beneficial to patients with H&N cancer during CT-RT. Hence, we designed the present study to evaluate the efficacy, in terms of treatment tolerance, toxicity and response, body weight, body composition, protein-calorie intake, quality of life (QoL), fatigue, muscle strength and immunological profile of the early systematic provision of ONSs enriched in immunonutrients compared to isonitrogenous standard blends, in H&N cancer patients undergoing CT-RT. Methods: This is a pragmatic, bicentric, randomized (1:1), parallel-group, open label, controlled, pilot clinical trial. Discussion: Many efforts are still to be taken to improve the efficacy of nutritional support in oncology. Immunonutrition represents a promising approach also in H&N cancer patients, but the evidence on its efficacy in improving clinical outcomes during CT-RT is still inconclusive. The present pilot study, which guarantees the early provision of nutritional assessment and support to all the enrolled patients in accordance with the recent guidelines and recommendations, could represent one of the first proofs of the clinical effectiveness of early oral immunonutrition in cancer patients undergoing CT-RT and could stimulate further large randomized trials, potentially resulting in the improvement of supportive care quality. Trial registration: This study is registered onClinicalTrials.gov Identifier: NCT04611113.